1991
DOI: 10.1111/j.1151-2916.1991.tb07818.x
|View full text |Cite
|
Sign up to set email alerts
|

Crack Stability and T‐Curves Due to Macroscopic Residual Compressive Stress Profiles

Abstract: Stabilization of the fracture process and resistance to strength degradation have been observed for materials with increasing T-curves. In this study, the possibility of using residual compressive stresses to induce crack stabilization is examined theoretically. Nonmonotonic forms for the residual compressive stress profiles are assumed. The stress intensity factors for linear through-the-thickness cracks subjected to these profiles are derived. The stress intensity factors are then used to construct the T-cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2
4

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 13 publications
0
18
2
4
Order By: Relevance
“…Therefore the authors propose that the lower reported baseline quantification range of the mean of the maximum deflection for the IPS e.max ® Press specimens was predominantly the result of specimen polishing regime inducing a tensile stress state across the surface defect integral which accounted for the observed surface convexity. The grinding process was multidirectional owing to the rotational spect of the machine during grinding, such that machining induced cracks and residual stresses are difficult to asses so that the nature of the interaction between these opposing factors is unclear in the ceramic literature [38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the authors propose that the lower reported baseline quantification range of the mean of the maximum deflection for the IPS e.max ® Press specimens was predominantly the result of specimen polishing regime inducing a tensile stress state across the surface defect integral which accounted for the observed surface convexity. The grinding process was multidirectional owing to the rotational spect of the machine during grinding, such that machining induced cracks and residual stresses are difficult to asses so that the nature of the interaction between these opposing factors is unclear in the ceramic literature [38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…Os aumentos da confiabilidade mecânica e termomecânica causados pela troca iônica, aplicada após a têmpera térmica, sugerem que o dielétrico temperado pelo método de dois estágios apresentou um perfil de tensão residual com um valor de máxima tensão de compressão deslocado a uma determinada profundidade da superfície, que dificultou o crescimento da trinca na região superficial por um comportamento equivalente ao de curva R crescente [17][18][19][20]. Aparentemente não há informações relativas à evolução do perfil de tensão residual no tratamento de têmpera térmica seguida de troca iônica.…”
Section: Efeito Da Troca Iônica Após Têmpera Térmicaunclassified
“…O perfil de aumento da tensão residual de compressão até o máximo valor na região próxima à superfície dificulta a propagação da trinca devido ao efeito de aumento da tenacidade à fratura aparente com o crescimento da trinca [19]. A ocorrência deste comportamento (curva R crescente) não é prevista no critério de resistência ao choque térmico R' (Equação 4), o que parece explicar, ao menos em parte, a não correspondência entre os resultados de propriedades mecânicas (Figura 5) e de choque térmico (Figura 7) dos dielétricos temperados por diferentes métodos.…”
Section: Efeito Da Troca Iônica Após Têmpera Térmicaunclassified
See 1 more Smart Citation
“…Uno está relacionado con la resistencia y la tenacidad de fractura (comparado con los correspondientes monolíticos) y otro con el modo de propagación de la grieta. Las tensiones residuales de compresión son generalmente beneficiosas en cuanto a la respuesta mecánica del material ya que se oponen al crecimiento de la grieta (12,13), dando lugar en algunos casos a la existencia de una tensión umbral de rotura (9). Por otra parte, las tensiones residuales de tracción afectarían negativamente la integridad estructural del material, y en caso de superar un valor crítico provocarían la aparición de "fisuras túnel" (tunneling cracks) reduciendo como consecuencia la resistencia mecánica del laminado (10,14).…”
Section: Introductionunclassified